A data challenge for Vietnamese abstractive multi-document summarization - Tran, Mai Vu; Le, Hoang Quynh; Can, Duy Cat; Nguyen, Quoc An (Journal of Computer Science and Cybernetics, 2024)
This paper provides an overview of the Vietnamese abstractive multi-document summarization shared task (AbMuSu) for Vietnamese news, which is hosted at the 9th annual workshop on Vietnamese Language and Speech Processing (VLSP 2022). The main goal of this shared task is to develop automated summarization systems that can generate abstractive summaries for a given set of documents on a specific topic. The input consists of several news documents on the same topic, and the output is a related abstractive summary. The focus of the AbMuSu shared task is solely on Vietnamese news summarization. To this end, a human-annotated dataset comprising 1,839 documents in 600 clusters, collected from Vietnamese news in 8 categories, has been developed. Participating models are evaluated and ranked based on their ROUGE2-F1 score, which is the most common evaluation metric for document summarization problems.